The Economic Foundation of Library Copyright Strategies in Europe - Vitiello, Giuseppe (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2021)
The author critically examines the evolution of open access libraries from the TULIP project (1991) to more recent developments. At the same time, he emphasises the role of libraries as key agents of national book policies through Public Lending Rights. After having shown the difference between the scholarly communication and the book chains, both in printed and digital form, the author points to the position that libraries hold on the distribution segment of the chains and how they are unable to turn power relations among actors to their own advantage. If content if king, organisations distributing content are normally king-makers, as the example of STM publishers clearly shows. Nevertheless, fragmentation and the assumption that what is good for libraries is also good for users do not allow libraries to understand the needs of the different stakeholders present in the value chain and provide appropriate services to them. This aspect is emphasised further in the book trade, where libraries have been hesitant in realising the economic foundation of copyright regulations which consists of trading off “the costs of limiting access to a work against the benefits of providing incentives to create the work in the first place” (Landes & Posner). After having examined library copyright strategies both in the book trade and in scholarly communication with a thorough discussion on (e-)lending and controlled digital lending, the author claims that copyright regulations are not written in the sky but on a solid foundation of economic forces which shape the book and information chains. Libraries’ strategies should aim to reinforce their relevance in the distribution segment and demonstrate their ability to provide services to all actors in the value chain. This role should also impact on the normalisation of library-publisher relations.